Madwomen: Gabriela Mistral’s “Locas mujeres”, published by La Nación of Buenos Aires (1941-1943) - Ariz Castillo, Yenny (Revista Chilena de Literatura, 2019)
A genetic analysis of the manuscripts and editions of six poems relating to the “Locas mujeres” section of Lagar (1954) by Gabriela Mistral, published between 1941 and 1943 by La Nación of Buenos Aires. “La dichosa”, “La desasida” and “La abandonada”, along with “La trocada” and “La tullida”, which were omitted from Lagar but included in manuscript indexes, and finally “La otra”, a poem which appears in the volume Poesías completas (1958) and also belongs to the “Locas mujeres” series. The present study allows us to dismiss the biographical interpretation of these texts as being linked to the death of Juan Miguel Godoy, a reading proposed by Palma Guillén and echoed by a section of Mistralian critics.